Bioeconomic Perspectives of Bacterial and Fungal Hydrolytic Enzymes: A Review - Adeoyo, Olusegun Richard (International Journal of Scientific Research in Biological Sciences, 2025)
Microorganisms have been in use as biotechnological tools since ancient time of human civilization. The extensive applications of microbial enzymes in the food, detergent, agricultural, textile, paper, pharmaceutical, and monitoring device industries have brought them international prominence. Enzyme mediated processes are rapidly gaining interest because of reduced process time, intake of low energy input, cost effective, nontoxic/eco-friendly properties, easy availability, fast production rate, and easiness of manipulation. Microbial enzymes with excellent performances function effectively in a variety of diverse physical and chemical environments. Hydrolytic enzymes (hydrolases) belong to a group of hydrolytic enzymes that are easily employed as biochemical catalysts. They utilize water as a hydroxyl group donor during the substrate breakdown. Bacteria and fungi are among microorganisms that have been extensively used for various enzymes production. Fungal enzymes in particular are generally recognized as safe (GRAS), they are favored above other microbial sources. Recent biotechnological development has made it possible to manipulate microbes with desired characteristics in large quantities to meet the increasing demand for industrial enzymes.